Politics, religion and violence in India - Guha Roy, Jaytilak
The author discusses the Gandhian perception and practice of religions where communalism is in total negation of religion. Explains the concept of secularism in India and how it differs from that in the west. In India religious fundamentalism culminates into communalisation of politics. In post-independence Indian politics, the secular national parties are also responsible for the increasing strength of communal forces in Indian politics. The incidence of communal riots which was only confined to urban areas has spread to rural areas as well. There is need for a thorough reapprisal of our political values, processes and the working of our secular democratic polity to solve the problem of increasing communal
Keywords: Political Party; Violence; Religion; Politics; Communalism - India